Highly sensitive glucose electrochemical sensor using sugar‐lectin interactions - Kyoko Sugiyama; Fumiya Sato; Sachiko Komatsu; Toshio Kamijo; Kentaro Yoshida; Yusuke Kawabe; Hiromi Nishikawa; Tsutomu Fujimura; Yasufumi Takahashi; Katsuhiko Sato (Electrochemical Science Advances)
Abstract In this study, glucose oxidase (GOx) was immobilized on the electrode surface by layer‐by‐layer and gel membrane technique and characterized the GOx immobilized film morphology, H2O2 permeability, and glucose response. Concanavalin A (Con A)‐GOx multilayer electrodes showed higher glucose‐related current response than GOx‐bovine serum albumin gel membrane‐coated electrode, a common modification method. The thin thickness of the Con A/GOx multilayer film efficiently catalyzed the enzymatic reaction, and H2O2 was produced near the electrode surface, resulting in an immediate electrode response.